Implications of Islamic Activities in Fostering Student Discipline in Schools (Study at SMP N 1 Sukoharjo and SMP N 2 Tawangsari) - Hidayati, Priska Nurul; Supriyanto, Eko; Muthoifin, Muthoifin (CV. Rayyan Dwi Bharata, 2024)
Character education to foster discipline needs to be pursued and implicated in formal and non-formal education. School is a formal educational institution that has the authority to shape student character. So that students can be fortified from the bad influence of association that can erode morals and morals. This type of research is a qualitative research with a phenomenological approach. Methods of data collection using interviews, observation, and documentation. Data analysis uses descriptive analysis, with conclusions drawn using a deductive method that departs from general events and then reduces them to specific parts. The results of this study are; 1) Forms of Islamic activities to foster student discipline which are carried out at SMP N 1 Sukoharjo, namely by carrying out Dhuha prayers, holding outing classes, behaving well, and getting used to smiling, greeting and greetings. The form of Islamic activities at SMP N 2 Tawangsari is carrying out BTA (Reading and Writing the Qur'an) activities independently, independent and joint tahfidz, spiritual Fridays, and 3S habits (smiles, greetings and greetings), dhuha prayers and midday prayers and the third is the habit of reading the kafaratul majlis prayer. 2) The steps for cultivating student discipline to foster discipline are carried out at SMP N 1 Sukoharjo, namely by compiling a disciplinary program and conducting socialization with student guardians. While the steps used by SMP N 2 Tawangsari are by compiling programs to support discipline, conducting socialization with student guardians, getting used to setting a good example to teachers and giving educational punishments to students who violate it. 3) The effectiveness of Islamic activities to foster discipline applied at SMP N 1 Sukoharjo is to have a long lasting impact on future students. Whereas SMP N 2 Tawangsari in carrying out Islamic activities to foster discipline has long-term effectiveness.